The "ready-to-hand" test: Diagnostic availability and usability in primary health care settings in Sierra Leone. - Alice Street; Eva Vernooij; Francess Koker; Mats Stage Baxter; Fatmata Bah; James Rogers; Momoh Gbetuwa; Mikashmi Kohli; Rashid Ansumana (Public Library of Science (PLoS), 2023)
This article assesses the availability of essential diagnostic tests in primary health care facilities in two districts in Sierra Leone. In addition to evaluating whether a test is physically present at a facility, it extends the concept of availability to include whether equipment is functional and whether infrastructure, systems, personnel and resources are in place to allow a particular test to be "ready to hand", that is, available for immediate use when needed. Between February 2019 and September 2019, a cross-sectional mixed-methods survey was conducted in all 40 Community Health Centres (CHCs) in Western Area, one of five principal divisions in Sierra Leone. The number of rapid diagnostic tests (RDTs) available ranged from 1-12, with 75% of facilities having 9 or less RDTs available out of a possible 17. While RDTs were overall more widely present than manual assays, there was wide variation between tests. The presence of RDTs at individual facilities was associated with having a permanent laboratory technician on staff. Despite CHCs being formally designated as providing laboratory services, no CHC fulfilled standard World Health Organisation (WHO) criteria for a laboratory. Only 9/40 (22.5%) CHCs had a designated laboratory space and a permanently employed laboratory technician. There was low availability of essential equipment and infrastructure. Supply chains were fragmented and unreliable, including a high dependency (>50%) on informal private sources for the majority of the available RDTs, consumables, and reagents. We conclude that the readiness of diagnostic services, including RDTs, depends on the presence and functionality of essential infrastructure, human resources, equipment and systems and that RDTs are not on their own a solution to infrastructural failings. Efforts to strengthen laboratory systems at the primary care level should take a holistic approach and focus on whether tests are "ready-to-hand" in addition to whether they are physically present.